Smallholder farmers' dissatisfaction with contract schemes in spite of economic benefits: Issues of mistrust and lack of transparency - Anette Ruml; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
Contract farming is typically seen as a useful mechanism to help smallholders. However, despite economic benefits, high dropout rates from contract schemes are commonplace. We use data from Ghana to show that smallholders benefit from a resource-providing contract in terms of higher yields and profits, but most of them still regret their decision to participate and would prefer to exit if they could. The main problem is insufficient information from the company. Farmers do not understand all contract details, which leads to mistrust. We argue that lack of transparency may explain high dropout rates in Ghana and other situations too.
Keywords: L29; L49; O12; O13; Q13; 330; contract farming; continuity; attrition; information; transparency